Mathematics Learning Assistance for Elementary School Children in Dayeuhluhur Village In The Collective Learning Program KKN Umtas - Karmila, Intan; Uswah, Fauziyatun Nurul; Syanissa, Meilani; Anggraeni, Dhita Mia; Romadhona, Rifqi; Putra, Reza Cahaya; Pabyana, Randi; Fauzi, Rizki Muhamad; Subagja, Andreas; Sutarya, Hana Hemalina; Nugraha, Mohammad Fahmi (AbdimasMu UMTAS, 2024)
The learning program with the UMTAS KKN is a Thematic KKN service program at the University of Muhammadiyah Tasikmalaya with the target of equivalent elementary school students living in Dayeuhluhur Hamlet, Dayeuhluhur Village, Dayeuhluhur District, Cilacap Regency. Where, the objectives of the program are: 1) Helping students understand material that has not been understood 2) Helping do homework given to students who have difficulty. With this learning program with the UMTAS KKN, students better understand the material that is considered difficult and is more helpful in doing school assignments. The results of the mentoring program are very helpful in increasing students' knowledge of learning mathematics, it can be seen from the pretest and posttest scores given to students